PROBLEM SOLVING APPROACH AND LEARNING MEDIA BASED ON VBA FOR EXCEL AS AN EFFORT TO IMPROVE THE MATHEMATICAL COMMUNICATION SKILLS OF ELEMENTARY SCHOOL STUDENTS - Citra Megiana Pertiwi; Nendi Rohaendi; Galih Dani Septiyan Rahayu (Jurnal Cakrawala Pendas, 2025)
Digital technology is one of the strongest driving forces in the modern economy, requiring the mastery of 21st-century skills. These skills can be developed through mathematics, as its learning process enhances students' strategic thinking. Mathematics should be taught from the elementary level to equip students with logical, analytical, systematic, critical thinking, and communication skills. Mathematical communication is especially important for elementary students to understand, express ideas, model problems, and find solutions. However, current evidence shows that students’ mathematical communication skills remain relatively low, partly due to the limited use of learning models and classroom activities designed to foster such abilities. One potential solution is the use of a problem-solving approach supported by VBA for Excel-based learning media. This combination can improve students’ mathematical understanding and enhance their 21st-century skills, particularly in mathematical communication. The use of VBA-based media provides students with visual and interactive tools to solve and communicate various mathematical problems. This study aims to examine the effectiveness of the problem-solving approach and VBA for Excel media in improving elementary students’ mathematical communication skills. A quasi-experimental method was used, applying a Pretest-Posttest Control Group Design in two classes at a public elementary school in Bandung, with sampling through Non-Probability Sampling techniques. The results showed that this approach effectively improved students’ mathematical communication skills. Moreover, the learning media helped optimize the learning process and received positive feedback from students.